Exploratory Grouping Along a Shared Oral-Health Burden Continuum in Children and Adolescents: An Age-Stratified Cluster Analysis - Narcis Mihaita Bugala; Smaranda-Adelina Bugala; Mihaela Jana Țuculină; Ancuta Ramona Camen; Alina Nicoleta Capitanescu; Dragos Cadea; Adrian Macovei; Loredana Selaru; Ana Maria Rica; Dana Maria Albulescu (Medicina, 2026)
Background and Objectives: Caries experience, plaque accumulation, gingival inflammation, and periodontal screening findings may coexist as manifestations of a shared oral-health burden. We examined whether these routinely recorded indicators form distinct multivariable profiles or primarily represent ordered levels along a common burden continuum in children and adolescents. Materials and Methods: This secondary exploratory analysis included 638 participants from a multicenter cross-sectional clinical database: 407 aged 6–12 years and 231 aged 13–19 years. Permanent-dentition Decayed, Missing, and Filled Teeth score, Plaque Index, Gingival Index, and Community Periodontal Index were standardized and analyzed separately by age stratum. Unsupervised K-means clustering compared solutions containing two to five groups to summarize participant-level patterns without imposing predefined clinical categories. Hierarchical Ward classification assessed algorithmic concordance; principal component analysis and a composite standardized burden score assessed dimensionality. Sensitivity analyses excluded the periodontal index or treated it as ordinal with Gower-distance partitioning around medoids, and 1000 repeated 80% subsamples assessed sampling stability using the adjusted Rand index. Results: A single principal component explained 91.0% of variance at 6–12 years and 91.8% at 13–19 years, with all four indicators loading strongly on the same dimension. Ordered cluster membership correlated closely with the composite burden score (Spearman ρ = 0.942 and 0.939; both p < 0.001). The retained low-, intermediate-, and high-burden groupings were highly consistent when the periodontal index was excluded or treated as ordinal and under repeated subsampling. In adolescents, a two-group alternative preserved the low- and high-burden extremes while dividing the intermediate group, indicating that the number of groups changes descriptive granularity rather than revealing a separate phenotype. Conclusions: The principal new finding is that four commonly used oral-health indicators converge on one dominant participant-level burden dimension rather than defining distinct clinical phenotypes. This supports an integrated epidemiological description of cumulative oral-health burden while cautioning against interpreting data-driven groups as diagnostic or treatment categories. The numerical group distributions are sample-specific and require external and longitudinal validation before being transferred to other populations or clinical decision-making.